Analisis Geometri Lereng Tambang Terbuka Menggunakan Metode Bishop disederhanakan pada Area Pit ASK Kabupaten Konawe Utara, Sulawesi Tenggara - Natasya Puteri Alquarima Ode; Laode Jonas Tugo; Asri Arifin (OPHIOLITE: Jurnal Geologi Terapan, 2025)
The study area utilizes open-pit mining methods across all its mining pits and plans to develop a new pit to increase annual production. Slope stability analysis is crucial for designing both single slopes and overall slopes. This research aims to identify the actual profile conditions of laterite nickel and the material characteristics within the ASK pit area, as well as to determine the factor of safety (FoS) and the probability of slope failure (PoF). The study applies slope stability analysis using the limit equilibrium method-Bishop simplified based on Mohr-Coulomb failure criteria. The results indicate that the limonite zone has a wet unit weight of 23.85 kN/m³, cohesion of 31.74 kPa, and an internal friction angle of 30.76°, while the saprolite zone has a wet unit weight of 22.20 kN/m³, cohesion of 26.25 kPa, and an internal friction angle of 29.22°. Based on analysis results, a safe single slope geometry can be applied with a slope angle ranging from 50° to 70°, a height of 6 meters, and a bench width between 1 to 3 meters. For the overall slope geometry, applying a slope angle of 38° to 42° with a bench width of 3 meters, the calculated FoS and PoF values indicate that the proposed slope design is still safe to use, with FoS > 1.1 and PoF between 25%–50%, are above the required standard threshold values.